Study on the SOVA decoding algorithm for Turbo codes based on modified path-metric - LIU Xing-cheng; ZHU Zhi (Tongxin xuebao)
Based on the analyses of the traditional SOVA algorithm,a novel SOVA decoding algorithm was proposed in order to avoid probability calculation of wrong path-metric. The reliability value of the last bit within the decoding trellis is adjusted based on the difference of the accumulated path-metrics among the survivor paths connected to register states. Theoretical computation and simulation results show that the proposed algorithm could greatly improve the BER per-formance of Turbo decoding.